Comparative study of conventional and topical heparin treatment in second degree burn patients for burn analgesia and wound healing. Issue 2 (March 2019) - Manzoor, Sobia; Khan, Farid Ahmad; Muhammad, Sohail; Qayyum, Rehan; Muhammad, Imran; Nazir, Umer; Bashir, Muhammad Mustehsan
Highlights: Conventional topical treatment for second degree burn is painful, complex, and uncomfortable for patient. Topical heparin treatment has been introduced as safe, cheap, and effective treatment for burns however available evidence of effectiveness is weak. Evidence of heparin effectiveness is weak and there is paucity of data from satisfactorily controlled trials. We found heparin treatment group had significantly better outcomes as compared to conventional treatment group. Treatment with topical heparin significantly accelerated wound healing, reduced pain scores and decreased analgesic requirements. The treatment with topical heparin is well-tolerated and is without higher adverse effects. Abstract: Objective: To compare clinical outcome of topical conventional with topical heparin treatment in 2nd degree or partial thickness (PTB) burn patients. Methods: Patients, between the ages of 14 and 60 years with 2nd degree burns involving <20%. Total body surface area (TBSA) on front of chest, abdomen and upper limbs excluding hands and lower limbs were enrolled from September 2015 to August 2016. Patients were randomized to conventional or heparin treatment groups. Clinical outcome measured were healed wound size, pain scores and total consumption of analgesic medication required to relieve pain. Safety of the treatment and adverse events were also measured Results: Out of 66 patient included in study mean (SD) age of participants was 27 (10) years, of which 59% were males. Mean (SD) TBSA burn was 14% (3) [23 (35%) had SPTB, and 43 (65%) had DPTB]. The burn injury was caused by flames in 68% and by hot liquids in 32% patients. There was no statistically significant difference in distribution of patients according to age, gender, TBSA burn, etiology or depth of burns in the two treatment groups. As compared to conventional treatment group, heparin treatment group had significantly better outcomes. Number of days needed for wound healing was significantly lower in the heparin group than the conventional group (SPTB 14 ± 1 vs. 20 ± 4 days; P-value <0.000 and for DPTB, 15 ± 3 vs. 19 ± 2 days; P-value <0.003). Mean pain score was also lower in the heparin group (for both SPTB and DPTB 3 ± 1 vs. 7 ± 1; P-value <0.000). Similarly, total consumption of analgesic medication was significantly less in the heparin group (53 ± 27 vs. 119 ± 15 mg; P-value <0.000 for SPTB and 46 ± 6 vs. 126 ± 12 mg; P-value <0.000 for DPTB). In both groups, no patient had wound infection, skin necrosis, leucopenia, thrombocytopenia, worsening renal function, or abnormal liver enzymes Conclusion: Treatment of second degree or partial thickness burns (PTB) with topical heparin is superior to conventional treatment in terms of wound healing as well as for pain control. The treatment with topical heparin is well-tolerated and is without higher adverse effects.